Pivmecillinam for Uncomplicated Lower Urinary Tract Infections Caused by Staphylococcus saprophyticus-Cumulative Observational Data from Four Recent Clinical Studies - Filip Jansåker; Marianne Bollestad; Ingvild Vik; Morten Lindbæk; Lars Bjerrum; Niels Frimodt-Møller; Jenny Dahl Knudsen (MDPI AG, 2019)
Objectives: To investigate pivmecillinam´s efficacy in uncomplicated lower urinary tract infection (UTI) caused by Staphylococcus saprophyticus—considered non-susceptible to mecillinam. Methods: Participants with confirmed UTIs caused by S. saprophyticus from four randomized controlled trials, where pivmecillinam was empirically given to females with symptoms of UTIs. The primary outcome was defined as a cumulative clinical effect—symptom resolution during the first eight days of therapy, without a recurrence of UTI symptoms in the long-term follow-up (approximately four weeks). Secondary outcomes included the bacteriological effect—elimination of the causative agent, with or without new uropathogenic bacteria present in the first control urine sample. Significant bacteriuria was defined as ≥103 bacteria/mL. The antibiotic susceptibility testing was done by disc diffusion methodology, according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST). Results: Seventy-four females (18−55 years) were empirically treated with pivmecillinam for UTIs caused by S. saphrophyticus (mean age 25 years; standard deviation (SD) 5.8). The cumulative clinical effect was 53/74 (72%), and the bacteriological effect was 51/59 (86%). Conclusion: Pivmecillinam showed a high clinical and bacteriological effect in UTIs caused by S. saprophyticus in these four clinical trials. The characterization of non-susceptibility for mecillinam regarding the treatment of UTIs caused by this common pathogen may need to be revised.